2009
DOI: 10.1016/j.brainres.2008.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Non-opioid antinociception produced by brain stem injections of improgan: Significance of local, but not cross-regional, cannabinoid mechanisms

Abstract: Improgan, a cimetidine derivative which lacks activity at known histamine, opioid or cannabinoid receptors, acts by an unknown mechanism in the periaqueductal gray (PAG) and raphe magnus (RM) to stimulate descending, analgesic circuits. These circuits may utilize cannabinoid mechanisms. To characterize further the nature of these circuits, the effects of intracerebral (i.c.) microinjections of rimonabant (a CB 1 receptor inverse agonist) were studied on antinociceptive responses following i.c. microinjections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…This model incorporates earlier evidence that -opioid and cannabinoid receptor 1 (CB 1 ) agonists act presynaptically to inhibit GABA release from terminals mediating the OFF-cell pause (Heinricher et al 1991(Heinricher et al , 1992Meng and Johansen 2004;Pan et al 1990;Vaughan et al 1999) and that morphine engages an excitatory input to OFF-cells (Heinricher et al 2001b). It also brings together the observations that improgan, which lacks affinity for known cannabinoid receptors, produces antinociception dependent on CB 1 receptors (Hough et al 2009b;Nalwalk et al 2006) and that CC12 blocks antinociception produced by both CB 1 -receptor agonists and improgan (Hough et al 2007). Finally, taken together with recent evidence implicating P450 epoxygenase activity in -opioid analgesic action (Conroy et al 2010), the present findings with CC12 suggest a P450 link between presynaptic -opioid receptor activation and inhibition of GABA release onto OFF-cells. The model proposes that CC12 exerts its effects presynaptically, inhibiting an epoxygenase necessary for both opioid-and cannabinoid-induced inhibition of GABA release.…”
Section: An Epoxygenase Model For Opioid Cannabinoid and Improgan Amentioning
confidence: 68%
“…This model incorporates earlier evidence that -opioid and cannabinoid receptor 1 (CB 1 ) agonists act presynaptically to inhibit GABA release from terminals mediating the OFF-cell pause (Heinricher et al 1991(Heinricher et al , 1992Meng and Johansen 2004;Pan et al 1990;Vaughan et al 1999) and that morphine engages an excitatory input to OFF-cells (Heinricher et al 2001b). It also brings together the observations that improgan, which lacks affinity for known cannabinoid receptors, produces antinociception dependent on CB 1 receptors (Hough et al 2009b;Nalwalk et al 2006) and that CC12 blocks antinociception produced by both CB 1 -receptor agonists and improgan (Hough et al 2007). Finally, taken together with recent evidence implicating P450 epoxygenase activity in -opioid analgesic action (Conroy et al 2010), the present findings with CC12 suggest a P450 link between presynaptic -opioid receptor activation and inhibition of GABA release onto OFF-cells. The model proposes that CC12 exerts its effects presynaptically, inhibiting an epoxygenase necessary for both opioid-and cannabinoid-induced inhibition of GABA release.…”
Section: An Epoxygenase Model For Opioid Cannabinoid and Improgan Amentioning
confidence: 68%
“…The best studied opioid-sensitive descending system has critical links in the periaqueductal gray and rostral ventromedial medulla (RVM). In recent extensive mapping studies, improgan was shown to act in both sites (Hough et al, 2001; Nalwalk et al, 2004; Hough et al, 2009). Further, the antinociceptive effect of icv improgan is abolished by functional lesions of the RVM, showing an essential requirement for activation of RVM neurons in the antinociceptive actions of improgan (Nalwalk et al, 2004).…”
mentioning
confidence: 99%
“…Presently, DMSO was used to dissolve CC44 in some experiments, but it is unlikely that use of this solvent invalidated the present conclusions. For example, published (Hough et al, 2009 vs. Nalwalk et al, 2004; Hough et al, 2002 vs. Hough et al, 2006) and unpublished studies from our lab found no differences in analgesic potency for improgan dissolved in saline as compared with DMSO. In addition, CC44 (i.c.v.)…”
Section: Discussionmentioning
confidence: 66%